Os descaminhos da reforma trabalhista no Brasil: processo histórico e os desafios atuais - Guiotti, Sandra Regina (2020)
This postgraduate research (Master level) has as its object of study the difficult dynamics of the labor reform in Brazil and the role of the Central Única dos Trabalhadores (CUT) in the process of discussion and approval of such reform. Initially, the paper analyzes the historical basis of labor regulation in Brazil, as well as a reflection on the concept of social regulation of labor. Subsequently, we look at CUT's positions on the institutional dynamics of labor reform, from the period of President Fernando Henrique Cardoso's government (1995- 2002) until its approval in November 2017, with emphasis on the period of President Lula da Silva's governments (2003-2010) and President Dilma Rousseff ́s governments (2011-August 2016). For the accomplishment of this dissertation, the chosen methodology was the qualitative research supported by interviews with the main actors of the mentioned process, besides the bibliographic research with the main authors and research institutes that address the labor reform and all the scope that the theme involves. In the final conclusions, an approach will be made around the paths taken by the flexibilization of labor relations that culminated in the approval of the Labor Reform in 2017 and how the CUT has positioned itself in the face of such trajectory, taking into account the internally transformations suffered in that syndicate that justified their positions.